Příklady z matematiky

Každé načítání stránky vám zadá nové příklady !




Jméno:_____________________________
 
X + Y - Z = 1127
Z + Y + X = 1233
Z + X - Y = 253

X=
Y=
Z=






X + Y - Z = 955
Z + Y + X = 1939
Z + X - Y = 599

X=
Y=
Z=






X + Y - Z = 368
Z + Y + X = 992
Z + X - Y = 314

X=
Y=
Z=






X + Y - Z = 646
Z + Y + X = 686
Z + X - Y = -64

X=
Y=
Z=






X + Y - Z = 1293
Z + Y + X = 1827
Z + X - Y = 147

X=
Y=
Z=






X + Y - Z = -180
Z + Y + X = 1436
Z + X - Y = 374

X=
Y=
Z=






X + Y - Z = 875
Z + Y + X = 1503
Z + X - Y = 25

X=
Y=
Z=






X + Y - Z = 1122
Z + Y + X = 2668
Z + X - Y = 748

X=
Y=
Z=






X + Y - Z = -34
Z + Y + X = 1844
Z + X - Y = 1662

X=
Y=
Z=